2016
DOI: 10.18632/oncotarget.13394
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy plus dendritic cells co-cultured with cytokine-induced killer cells versus chemotherapy alone to treat advanced non-small-cell lung cancer: A meta-analysis

Abstract: This study was aimed to investigate the efficacy and safety of the combination treatment of dendritic cells co-cultured with cytokine-induced killer cells and chemotherapy for patients with advanced non-small-cell lung cancer (NSCLC). Literatures were searched from the Cochrane Library Central, PubMed, Web of Science and EMBASE. The primary endpoint of interest was overall survival (OS), and secondary endpoints were disease control rate (DCR) and progression free survival (PFS). Finally 7 trials published betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 35 publications
2
37
0
Order By: Relevance
“…An increasing amount of studies demonstrated that CIK cell-based immunotherapy is a promising new treatment modality with the potential of improving the prognosis of cancer patients (18)(19)(20)(21)(22)(23)(24)26,27). A study from the International Registry reported the results of 11 CIK cell treatment trials for a variety of cancers, including hepatocellular carcinoma, gastric cancer and Hodgkin or non-Hodgkin lymphoma, and demonstrated a total response rate of 91/384 reported patients; 161 patients had stable disease and 129 patients had progressive disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing amount of studies demonstrated that CIK cell-based immunotherapy is a promising new treatment modality with the potential of improving the prognosis of cancer patients (18)(19)(20)(21)(22)(23)(24)26,27). A study from the International Registry reported the results of 11 CIK cell treatment trials for a variety of cancers, including hepatocellular carcinoma, gastric cancer and Hodgkin or non-Hodgkin lymphoma, and demonstrated a total response rate of 91/384 reported patients; 161 patients had stable disease and 129 patients had progressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…and enhanced by dendritic cells (DCs), which are the main antigen-presenting cells (18,19). DCs present tumor antigens through MHCII molecules, preventing the immune escape of tumor cells.…”
Section: Enhanced Antitumor Effects and Improved Immune Status Of Denmentioning
confidence: 99%
“…At present, surgery, radiotherapy and chemotherapy are most widely used for EC 4. However, their application is limited by the failure to thoroughly eliminate tumor cells, drug resistance and other adverse effects 5,6. Therefore, a more effective and safer therapeutic method is urgently required.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, immunotherapy has been rising rapidly and is considered the fourth powerful therapeutic method after surgery, radiotherapy and chemotherapy 6. Cancer immunotherapy is accomplished in multiple ways, including manipulation of the immune system through the use of immune agents, such as vaccines,7 cytokines,8 checkpoint inhibitors (including anti-programmed death 1 [PD-1]/PD-ligand 1 [PD-L1] antibodies and anti-cytotoxic T-lymphocyte-associated antigen (CTLA)-4 antibodies),9,10 kinase inhibitors (such as apatinib and gefitinib)11,12 and immune cells 13–19.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation